High-speed railway, market access, and economic growth - Wei Zou; Liangheng Chen; Junke Xiong (Asian Development Bank Institute (ADBI), 2018)
This paper establishes a general equilibrium trade model and adopts the "market access" approach to measure the impact of the high-speed railway (HSR) network on the economic growth of 110 of the main prefecture-level cities of the People's Republic of China, for which we manually collect the pairwise travel distances and railway speeds to calculate the market access (MA). The empirical results show that the launch of the HSR exerts significant positive effects on growth; specifically, a 1% increase in MA leads to an increase in real income of 0.123% (controlling the region fixed effect) or 0.121% (controlling the province fixed effect). Counterfactual econometric analysis indicates that, if all the HSR were removed in 2015, the market access would fall by an average of 76.2% and the aggregate real income would decline by up to 9.4%. The growth effect of the HSR varies across cities, and the HSR has a more prominent impact on services than on manufacturing. The conclusion remains valid after a series of robustness tests.
Keywords: F14; R11; R42; 330; high-speed railway; transport infrastructure; market access; economic growth; PRC